Is Preoperative Pain Duration Important in Spinal Cord Stimulation? A Comparison Between Tonic and Burst Stimulation. Issue 1 (21st October 2014) - De Ridder, Dirk; Vancamp, Tim; Lenders, Mathieu W.P.M.; De Vos, Cecile C.; Vanneste, Sven
<x xml:space="preserve">Abstract</x> Objective Conflicting data have been published as to whether the success rate of spinal cord stimulation (SCS) is inversely proportional to the time interval from the initial onset of symptoms to implantation. Recently, a new stimulation design called burst stimulation has been developed that seems to exert its effect by modulating both the medial and lateral pain pathways and has a better effect than tonic stimulation on global pain, back pain, and limb pain. Materials and Methods We analyzed the effect of preoperative pain duration on the degree of pain suppression by both tonic and burst stimulation in a group of patients (n = 49) who underwent both tonic and burst SCS. Results Using Pearson correlation analysis and controlling for age and duration of SCS, no correlation could be found between the preoperative pain duration and the success of SCS, either for tonic or for burst SCS, as defined by a numeric rating scale for pain. Using a different analysis method, dividing patients into groups according to preoperative pain duration, the same absence of influence was found. Pain was better suppressed by burst stimulation than tonic stimulation, irrespective of the preoperative pain duration. Conclusions These results suggest that the duration of pain is not an exclusion criterion for SCS and that similar success rates can be obtained for longstanding pain and pain of more recent onset.